THE DEVELOPMENT OF TECHNOLOGY OF FUNCTIONAL BEVERAGES BASED ON WHEY AND PLANT EXTRACTS - Cherevach E.I.; Tenkovskaya L.A. (Техника и технология пищевых производств)
Nowadays, the range diversification of functional whey-based beverages has lots of interest. The use of plant extracts or their compositions in the formulation of such beverages is relevant as it increases concentrations of biologically active substances including those having an antioxidant effect. Therefore, the purpose of this study was the development a technology of functional whey-based beverages and compositions of plant extracts from the Far East region and mangosteen (Garcinia mangostana L. ). The extraction of biologically active substances from hips, cranberries, black chokeberry berries, Amur grapes, actinidia kolomikta berries is optimized with the method of mathematical modeling; the synergetic antioxidant effect of the extracts’ compositions with an extract of mangosteen has been established. The recipes and technological process of beverages «ACTIVE» have been developed; the concentrations of stabilizers and fillers, providing a stable gel-like structure of the beverage have been determined. Using the complex of parameters the quality evaluation of whey-based beverages compared to the analogue has been done. The proposed technology allows us to obtain gelled whey-based beverages, which are natural food products. They have higher organoleptic characteristics, significant concentrations of functional antioxidant ingredients (flavonoids, xanthones, and vitamin C) and storage time compared to the analogue.